Fetus in Feto: A Case Study with Explanation - Nath Datta, Atindra (BOHR International Journal of General and Internal Medicine, 2022)
A 13 year boy was operated (exploratory laparotomy) for unexplained pain abdomen and a live fetus was found attached to left kidney. It was explained to be a case of identical twin. In twins, the placental capillaries anastomose very intricately so that one fetus may draw more blood resulting to deprivation of blood supply to other fetus who may end up to no supply later. But it did not kill the deprived fetus, but remain arrested in the erstwhile embryonic stage. While remaining in extraperitoneal space the deprived fetus is joined by herniated intestines of healthy fetus in physiological hernia. Later when intestines return to abdominal cavity (by creating extra space in abdomen) of heathy fetus the stunted fetus accompany intestines and managed to reach within abdominal cavity of healthy baby.